The Effects of Clients' Characteristics on Auditor Independence: A Perceptual Study - Rusmanto, Toto (International Journal of Economics and Financial Issues, 2017)
The objective of this research is to investigate the effect of clients' characteristics -including clients' reputation, clients' audit committee and clients fee contribution- on auditor independence. This research uses qualitative approach. Semi-structured interviews with auditors have been conducted. Interviews data were summarized, pattern coded, (Miles and Huberman, 1984) and then analyzed through description, analysis and interpretation (Walcott, 1994). The research result is expected to be able to explain auditors perceptions on their clients' characteristics whether their independence are affected by clients' reputation, clients' audit committee and clients' fee contribution. By doing this study, it will be able to see how auditor perceive and treat their clients to do audit works while at the same time they have to maintain their auditor independence. Keywords: Client' Reputation, Audit Committee, Fee Contribution JEL Classifications: M4, M42